Pengembangan Augmented Reality Pengenalan Hewan Berdasarkan Jenis Makanannya untuk Siswa Sekolah Dasar - Riski Sokani; Dian Aminudin; Dwi Ratnawati (Jurnal Teknologi, 2023)
A less interesting learning process resulted in students feeling bored with the material presented. Therefore this study aims to create interesting learning media so that students are interested in learning the material optimally. The research method used by the author uses the Multimedia Development Live Cycle (MDLC) system development method developed by Luther. The Multimedia Development Live Cycle (MDLC) is carried out based on six stages, namely concept, design, material collection, assembly, testing, and distribution. This research produces a product in the form of an Augmented Reality application to classify animals based on the type of food for elementary school children. The results of the Black Box test can be concluded that the application can run well. The results of the feasibility test calculation obtained a score of 81.31% included in the very feasible category. The products used in this study were declared very suitable for use by elementary school children and used as learning media so that they could help students' understanding processes and foster students' interest and enthusiasm for learning.